Embryogenesis of the damselfly Euphaea yayeyamana Oguma (Insecta: Odonata: Euphaeidae), with special reference to the formation of their larval abdominal "gill‐like" appendages. Issue 3 (11th June 2020) - Suzuki, Kohei; Watanabe, Yoko; Tojo, Koji
Abstract: The acquisition of wings in insects is the most significant subject in considering the diversification and adaptive radiation of insects, that is, the "macro‐evolution" of insects. In the discussion of the origin of insect wings, Palaeoptera has attracted particular attention in phylogenetic and evolutionary studies. In particular, Ephemeroptera have segmental gill‐structures on their abdominal segments during their nymphal stage, and these have been noted in discussions regarding their homology and/or serial homology between wings, gills and appendages. Although Odonata has received little attention in the course of these discussions, there are cases of segmental gill‐like structures on their abdomen in the two families, Euphaeidae and Polythoridae. Under such cirumstances, in this study, the embryological developmental process in Euphaea yayeyamana of Euphaeidae was observed, focusing on the formation process of the gill‐like structures. As a result, it was revealed that four of the seven pairs of gill‐like projection structures started their visible formation within the middle stages of embryonic development, and the remaining three pairs developed during the early stages of post‐embryogenesis. Some joint‐like structures existed in all of the gill‐like projections. It was revealed that muscle tissue was interposed within these protrusions and that all of the projections themselves fully articulated, and that the nervous system was extended into the protrusions. All of the gill‐like projections strongly suggested their homology with the cephalic and thoracic appendages, when we considered them with regard to their serial homology based on the topology of their formation position. Abstract : We describe in detail the embryogenesis of one damselfly and suggest that their abdominal gill‐like projections were homologus to the appendages. The identification of abdominal appendages in Palaeoptera is a significant finding in the context of the relationship between these structures and ephemeropteran abdominal gills, and the origin of insect wings.